(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
This article discusses the need to reform the world’s freely convertible currency exchange system. Current freely convertible currencies are based on the economy and monetary system of certain countries, and it is not possible for other countries to see this system transparently. This situation is bound to provoke protests. The article states that a new system should be created that will allow to determine the value of the currency on the basis of the principle of transparency for all. It also outlines the advantages of restricting the movement of states as freely convertible currencies.